Vagus Nerve Stimulation Affects Pain Perception in Depressed Adults. (1st March 2005) - Borckardt, Jeffrey J; Kozel, F Andrew; Anderson, Berry; Walker, Angela; George, Mark S
Abstract : BACKGROUND: Previous research suggests that vagus nerve stimulation (VNS) affects pain perception in epilepsy patients, with acute VNS decreasing pain thresholds and chronic VNS treatment increasing pain thresholds. However, no studies have investigated the effects of VNS on pain perception in chronically depressed adults, nor have controlled, systematic investigations been published on the differential effects of certain VNS device parameters on pain perception. OBJECTIVES: The present study tried to replicate the results of previous research showing acute pronociceptive effects of VNS and determine the effects of various device parameter settings on pain tolerance. The present study also investigated the relationship among patients' levels of depression, duration of VNS treatment and VNS-induced changes in pain perception. METHODS: A thermal pain challenge task was used to determine pain tolerance during VNS device activation using different combinations of VNS device parameter settings within subjects undergoing VNS therapy for chronic depression. RESULTS: Significant pronociceptive effects were found for acute VNS activation. Individual differences were found with respect to the VNS settings associated with the largest changes in pain perception. Severity of depression was inversely related to baseline pain tolerance, but depression severity was unrelated to VNS-induced acute changes in pain tolerance, as was the length of time participants had been undergoing VNS treatment. CONCLUSIONS: VNS appears to affect pain perception in depressed adults. Different VNS parameter settings may be associated with unique effects from patient to patient. More studies are needed to determine the long-term effects of VNS on pain perception.